A review on integration of speak up in CLABSI prevention and amar makruf nahi mungkar - Hamrah, Muhammad Hamzihadi; Mohd Ali, Noor Azizah; Daud, Azlina; Mohd Mokhtar, Hanida Hani (Academic Inspired Network, 2024)
Central Line-Associated Bloodstream Infections (CLABSIs) present a significant challenge in healthcare, leading to increased morbidity, mortality, and costs. Effective prevention strategies are essential, and one promising approach is the speak up initiative, which encourages healthcare professionals to voice concerns and adhere to best practices. This paper explores the integration of the speak up initiative with the Islamic principles of Amar Makruf Nahi Mungkar (promoting good and preventing evil) to enhance CLABSI prevention efforts. Methodology: A literature review was conducted using databases, including Google Scholar, Emerald Insight, and Medline, limited to articles published in English between 2014 and 2024. Keywords included CLABSI prevention, Speak Up, Amar Makruf Nahi Mungkar, and Enjoining Good and Preventing Evil. Results: Findings highlight the scope of research across selected topics, with significant attention on CLABSI prevention and the speak up initiative, while fewer articles addressed the ethical concepts of Amar Makruf Nahi Mungkar and Enjoining Good and Preventing Evil. Discussion: Integrating the speak up initiative with Amar Makruf Nahi Mungkar emphasizes proactive communication and ethical responsibility in healthcare, encouraging professionals to voice concerns and adhere to best practices while promoting accountability and patient empowerment. Conclusion: In summary, combining the speak up initiative with Amar Makruf Nahi Mungkar enhances CLABSI prevention efforts, fostering a culture of open communication and ethical responsibility that leads to improved patient safety and care quality.